Pengaruh Model Role Playing dengan Permainan Tradisional Pasaran terhadap Kemampuan Numerik Siswa - Auliya Cindy Andriyani; Himmatul Ulya; M. Syafruddin Kuryanto (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Education has an important role in the development and development of a nation to civilize humans. The process of transferring knowledge takes place continuously that occurs systematically from one person to another. The Transfer of knowledge that occurs is expected to change the attitude, behavior, morals, ethics, and maturity of one's thinking. Learning that uses a variety of learning methods provides a fun transfer of knowledge by involving teachers and students that is carried out in the world of education at school. Based on observations made by researchers, it was found that the low numerical ability of students in the study, so the researchers conducted a study using a role playing model using traditional market games in the learning process. This study aims to analyze the effect of role playing models with traditional games of the market on the numerical ability of students on the average difference pretest-posttest. Actors in the game markets are children who have not been so burdened with activities that require energy and mind. This study is a pre-experimental design with one-group pretest-posttest design. The study was conducted in Class V SDN 01 Gemiring Kidul, Nalumsari, Jepara. The independent variable of this research is role playing model using traditional market games, while the dependent variable is the numerical ability of students. Data analysis techniques used Are t test on pretest and posttest results with a significance level of 5%. Based on the results obtained it can be concluded that the application of role playing model using traditional market games have an influence on the numerical ability of students, with the average numerical ability of students before being given treatment of 52.5 and after using the role playing model with traditional market games of 82.83. The difference in the average result has a difference of 30.33 which shows a significant effect on students ' numerical ability.